Scientific teaching of theater performance for older adults - Rojas Lobo, David Esteban (2018)
This article arises from the experience of the author of five years working in theater with Seniors (PAM), both in urban and rural areas. In addition, the academic experience in Program Evaluation and Development Projects is added with an emphasis on culture, inputs that allow us to recognize the need to design, with the gerontological approach, teaching processes of theatrical performance. The purpose is to provide a baseline for the academy and institutions, recognizing some of the weaknesses and strengths of this population. To this end, it is essential to collect relevant data from apprentices, such as sociodemographic and socio-economic variables, but above all, cultural aspects such as value systems, interests, entertainment and religious beliefs, among others. The purpose is to generate an important methodological basis for analysis and the creation of the acting actions. The results are a methodology applied to teaching theater with PAM that contributes to a dignified and active old age.